Intra- and Inter-Limb Strength Asymmetry in Soccer: A Comparison of Professional and Under-18 Players - Chris Bishop; Giuseppe Coratella; Marco Beato (MDPI AG, 2021)
(1) Background: the present study examined the isokinetic peak torque exerted by both knee extensors and flexors, anterior-posterior imbalance and the magnitude and direction of inter-limb asymmetry in professional and academy soccer players. (2) Methods: one hundred soccer players (professional = 50, elite academy = 50) volunteered to take part in this investigation. An isokinetic dynamometer was used to measure the knee extensor (quadriceps) and flexors muscle (hamstrings) torques of the limbs as well as inter-limb asymmetries-using a standard percentage difference equation. (3) Results: professional players exhibited significantly greater (effect size [ES] = large) strength levels in the quadriceps and hamstrings under both testing conditions, significantly higher (small to moderate) intra-limb ratio values for 60°·s−1 but not for the 300°·s−1 test condition, significantly (small to moderate) lower inter-limb asymmetry values for all test conditions, with the exception of the hamstrings at 60°·s−1 and the direction of asymmetry was poor to slight, indicating that limb dominance was rarely the same between groups. (4) Conclusions: this study shows that isokinetic assessments, i.e., peak torque exerted by both knee extensors and flexors and intra-limb ratio, and the subsequent inter-limb asymmetry, i.e., magnitude and direction, can differentiate between professional and academy soccer players.